The Framing Analysis of Gibran Rakabuming Raka's Coverage as Vice Presidential Candidate on Tribunnews.com - Rochmawati, Novia; Pawito, Pawito; Hastjarjo, Sri (PT FORMOSA CENDEKIA GLOBAL, 2023)
The media shapes diverse political messages, influencing public opinion significantly. Mass media, deeply involved in political discourse creation, presents politically generated news of high value. Framing, a mass media process, influences public opinion. This study analyzes framing in Gibran Rakabuming Raka's coverage on Tribunnews.com post his candidacy as Vice President in the 2024 Election. Employing a qualitative approach based on Zhongdang Pan and Gerald M. Kosick's framework, it examines syntactic, script, thematic, and rhetorical structures. The findings highlight the emphasis on factual presentation via quotations (syntactic), compliance with the 5W+1H elements (script), Gibran's thematic emphasis on evidence addressing public queries, and Tribunnews.com's journalists' tendency to portray actual conditions, including statistical data (rhetoric).